2021
DOI: 10.1111/jocd.14358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local vibrotherapy in sitting or lying position in two time protocols on the cellulite grade and change of body circumferences in women with cellulite

Abstract: Background: Vibrotherapy is becoming a new tool which can help to improve aesthetic appearance. One of its basic uses in cosmetology is eliminating cellulite changes. Aim:The aim of the study was to analyze the effect of a 3-week series of local vibrotherapy in two positions and in two time protocols on selected body circumferences, WHR, WHtR and BAI, and the grade of cellulite. Patients and Methods: Volunteers underwent vibration treatments in a lying or sitting position for 30 or 60 minutes a day, for 3 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As indicated in our study, the action of vibration is dose-dependent regarding time range (the observed differences between the action of 30- and 60-min treatments). However, the dose-dependence of the action of the vibrations is not manifested in all its effects [ 7 ]. In this project, the series of treatments used allowed for the reduction of the waist circumference and significant changes in WHR (waist to hip ratio) and WHtR (waist to height ratio) regardless of the time of a single treatment (30 or 60 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in our study, the action of vibration is dose-dependent regarding time range (the observed differences between the action of 30- and 60-min treatments). However, the dose-dependence of the action of the vibrations is not manifested in all its effects [ 7 ]. In this project, the series of treatments used allowed for the reduction of the waist circumference and significant changes in WHR (waist to hip ratio) and WHtR (waist to height ratio) regardless of the time of a single treatment (30 or 60 min).…”
Section: Discussionmentioning
confidence: 99%
“…Vibrotherapy is one of the methods for minimizing or reducing the visibility of cellulite. It can be used in the form of monotherapy [ 4 , 5 , 6 , 7 ] or combined with other treatment forms, such as non-focused ultrasound with Aussie current and low-level laser therapy [ 8 , 9 ]. The medical application of this physical stimulus is a relatively old idea.…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, even today the number of papers regarding the characterization of the area affected by cellulite is poor. 20,[33][34][35][36][37][38][39][40] Independently from cellulite, the anatomy and morphology of gluteal femoral area are still lack of knowledge. 41,42 Published study described the anatomy and connective fibers organization of this area with different techniques, such as ultrasound and x-ray characterized by lower resolution than 7 T-MRI, described in this study.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Some studies proposed a very unusual description of subcutaneous adipose tissue anatomy, evidencing a different distribution of connective septa among female and male. [36][37][38][39][40][41][42][43][44] The female connective septa were described with parallel orientation, while in male was proposed a crossing distribution of the connective structure. 41,42 With the cellulite progression, parallel connective septa caused a pressure on adipose lobules, that protruding on the skin, causing the orange peel aspect.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation